Tiered Governance and Demonetization: The Shifting Terms of Labor and Compensation in the Platform Economy. (June 2020) - Caplan, Robyn; Gillespie, Tarleton
Social media platforms have profoundly transformed cultural production, in part by restructuring the terms by which culture is distributed and paid for. In this article, we examine the YouTube Partner Program and the controversies around the "demonetization" of videos, to understand these arrangements and what happens when they shift beneath creators' feet. We use the testimony of YouTubers, provided in their own videos, to understand how creators square the contradiction between YouTube's increasingly cautious rules regarding "advertiser-friendly" content, its shifting financial and algorithmic incentive structure, and its stated values as an open platform of expression. We examine YouTube's tiered governance strategy, in which different users are offered different sets of rules, different material resources, and different procedural protections when content is demonetized. And we examine how, especially when the details of that tiered governance are ambiguous or poorly conveyed, creators develop their own theories for why their content has been demonetized—which can provide some creators a tactical opportunity to advance politically motivated accusations of bias against the platform.